PENGEMBANGAN PROGRAM SUPERVISI PENDIDIKAN ISLAM, PENINGKATAN MANAGERIAL KEPALA SEKOLAH MIS AN-NUR - Paramida, Cici (STIT Ibnu Rusyd Tanah Grogot, 2025)
Managerial supervision in the context of education has a very important role in improving effective learning in schools. Managerial supervision involves the principal and other school staff in managing various aspects of education that contribute to the quality of learning. The purpose of this study is to understand the concept of managerial supervision and the role of supervision in its implementation so that it can contribute to improving effective learning in schools. In the problems found in MIS An-Nur on a smaller scale, the principal must have the skills needed to ensure the conditions needed for the progress of his institution in order to carry out his role as a supervisor. So, it is expected that the different educational goals at the school level are achieved well. The principal as a supervisor must consistently make efforts to achieve the level of progress mentioned above. The head of the madrasah must carefully consider every aspect of this achievement, including whether or not all the prerequisites for achieving the goal are met. Therefore, it can be said that the duties of the principal are more than just acting as an administrator. They also include supervising, encouraging, and stimulating the performance of instructors and other staff members to maintain a positive learning environment. The results of the study indicate that managerial supervision can have a positive influence in improving effective school management. Through managerial supervision, the principal can carry out effective supervision and management of aspects of education, such as curriculum, students, facilities and infrastructure, school and community relations, financial administration, personnel, culture, and the school environment. In its implementation, managerial supervision requires a systematic and planned approach. The principal needs to have good managerial skills in managing and leading school staff, as well as implementing effective supervision practices. In addition, managerial supervision also requires good collaboration and communication between the principal, teachers, and other school staff.